The influence of large classes in the English language teaching-learning process in Ecuadorian high schools - Castillo Castillo, Alexandra (2014)
The research is about the influence of large classes in the English teaching-learning process in Ecuadorian high schools, and its purpose is to determine how large classes affect or not the English language teaching-learning process. The study was conducted in five classrooms, from 8th basic to 3rd senior year, that were selected from two public high school in the city of Cariamanga; all the selected courses had over 35 students. The sample consisted of 179 participants whose ages ranged between 12 and 17 years old. Qualitative and quantitative methods were used as the general approach of this study. Students surveys were also applied to find out aspects that influence on the English language teaching-learning process. Mainly the results showed that students answers were generally positive regarding the instructional implications of large classes. Among social implications was shown that teachers who work with large classes have problems when remembering students names. Finally, it was found that large classes affect the quality of classroom atmosphere, students confidence to speak in class, and the teachers level of attention towards their students.